Aromas y sabores para la industria de alimentos - Paredes Galvez, Carlos (2022)
The present work on aromas and flavors in the food industry has the objective of knowing how to define between aroma and flavor and to know the mechanism of its formation of these aromas from both microorganisms that can be fungi, bacteria, yeasts, generating different odors or aromas. natural that have the same characteristics that do not alter the quality of food products, maintaining the taste, bitter, acid, sweet and umami, which are generated by chemical substances that are generated by olfactory sensations present in the nose and mouth of every human being . Likewise, when a person is older, they lose that ability to be a good evaluator, because a young person has all the sensitive endings in the tongue and nose, making it, and if they are a trained person, a good evaluator. The food industry currently has a great challenge which is to produce aromas and flavors using natural raw materials, thus having functional, healthy food products, with all their nutritional chemical compounds, that the human body can take advantage of completely healthy. This industry worldwide is the one that has grown the most in the last decade, and we must know how to take advantage of it for its use in the improvement of products that improve people's lives as well as improve the quality of life of the human being, in that way. contribute to the disappearance of synthetic products that do not contribute anything good to the human body.